Experimental and analytical study of pvc confined concrete cylinders - Abdulrazzaq Azeez, Alyaa; Jamaluddin, Norwati; Abd Rahman, Norashidah; Hassen, Douread Raheem; Attiyah, Ali Naji (Medwell Journals, 2018)
This study presents results of an experimental research on the concrete filled Poly Vinyl Chloride (PVC) tubes short columns with various typical strengths of the infill concrete; C20, C25, C40. A total of 36 Concrete Filled Tube columns using PVC tubes (CFT PVC) were tested to investigate the column’s behaviour and 18 cylinder concrete column. The columns are 200 mm height, 100 mm external diameter and 3.5 and 4.8 mm tube thickness. The results presented include the maximum axial load, thickness effect, the mode of failure and concrete compressive strength effect. The column resistance shows an increment of between 32.24-83.25% higher compared to the control column specimens. The design equations for the CFT PVC tube columns are proposed.